2022
DOI: 10.1101/2022.05.18.492465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular senescence in malignant cells promotes tumor progression in mouse and patient Glioblastoma

Abstract: Glioblastoma (GBM) is the most common primary malignant brain tumor in adults, yet it remains refractory to systemic therapy. Elimination of senescent cells has emerged as a promising new treatment approach against cancer. Here, we investigated the contribution of senescent cells to GBM progression. Senescent cells were identified in patient and mouse GBMs. Partial removal of p16Ink4a-expressing malignant senescent cells, which make up less than 7 % of the tumor, modified the tumor ecosystem and improved the s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Efforts are currently underway to better characterize TAM subtypes, ligand–receptor pairs, and immune checkpoints expressed by these cells [ 66 ]. It is becoming clear that glioblastoma progression requires not only genetic drivers but also microenvironment interactions [ 9 ▪▪ , 10 ▪▪ , 11 ▪ , 67 ▪ ]. While most of the work on immunoevading mechanisms and myeloid interactions has been done in MES-like gliomas [ 13 ▪ , 14 ▪ , 18 , 67 ▪ ], the immunomodulatory mechanisms operating in low-grade and IDH-mutant gliomas remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Efforts are currently underway to better characterize TAM subtypes, ligand–receptor pairs, and immune checkpoints expressed by these cells [ 66 ]. It is becoming clear that glioblastoma progression requires not only genetic drivers but also microenvironment interactions [ 9 ▪▪ , 10 ▪▪ , 11 ▪ , 67 ▪ ]. While most of the work on immunoevading mechanisms and myeloid interactions has been done in MES-like gliomas [ 13 ▪ , 14 ▪ , 18 , 67 ▪ ], the immunomodulatory mechanisms operating in low-grade and IDH-mutant gliomas remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Multiomics analyses of glioma cells at single-cell resolution revealed that intratumoral epigenetic diversity (but not genomic alterations alone) accounts for adaptive changes to environmental stimuli such as hypoxia and irradiation, leading to cell-state transitions [ 8 ▪ , 9 ▪▪ ]. Additional characterization of glioblastomas by spatially resolved transcriptomics showed that inflammation and hypoxia, as well as changes in metabolic activity and the neural environment contribute to the transcriptional heterogeneity that characterizes the four cellular archetypes [ 11 ▪ ]. In particular, expression of potassium channels and metabotropic glutamate receptors are important for the transition between OPC-like and NPC-like tumors, whereas hypoxia leads to genomic instability in MES-like subtype [ 10 ▪▪ ].…”
Section: Intratumoral Heterogeneity Of Idh-wildtype Gliomasmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in certain tumor types, the (abundant) presence of OIS or expression of senescence-associated markers is also linked to worse prognosis [132,197,221,237,238,248]. Perhaps even more surprisingly, both absence and extensive presence of senescence in CRC was associated with negative prognosis whereas moderate presence was associated with the best prognosis [174], demonstrating that an extensive senescence burden can paradoxically impair clinical outcome in contrast to a moderate senescence burden.…”
Section: Senescence Burdenmentioning
confidence: 99%